A-site deficiency in La0.5Ca0.5MnO3-δ cathode allows high performance for proton-conducting solid oxide fuel cells. Issue 23 (1st December 2022) - He, Shoucheng; Dai, Hailu; Bi, Lei
Abstract: The A-site deficiency strategy is proposed for the ABO3 perovskite structure La0.5 Ca0.5 MnO3-δ (LCM), which provides higher performance as a cathode for proton-conducting solid oxide fuel cells (H-SOFCs). The A-site deficiency can happen at the La site or the Ca site, and either can enhance the oxygen vacancy content and the oxygen reduction reaction (ORR) ability compared with the traditional LCM. Comparatively, the performance improvement for the La-site defective material is more profound, resulting in to a high cell performance of 1265 mW cm −2 at 700 °C, the largest ever reported for single-phase Mn-based cathode cells. The analysis for the cell resistances reveals that the A-site deficiency can promote the cathode reaction, leading to smaller cathode polarization resistances. The La-site deficient cathode shows the smallest polarization resistances under both the open circuit voltage (OCV) condition and loading. Furthermore, the A-site defective materials possess excellent chemical stability against CO2 and H2 O, making them attractive cathode candidates for high-performance H-SOFCs.